2012
DOI: 10.1080/00380768.2011.650134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tillage and winter cover cropping on microbial substrate-induced respiration and soil aggregation in two Japanese fields

Abstract: We hypothesized that cover cropping could increase soil microbial activities under various tillage systems and that increased microbial activities would improve soil properties. Soil sampling was conducted at two fields in Japan in 2009. At the Ibaraki field (Andosol, clay loam), three tillage practices (no-tillage, plowing to 30 cm, and rotary tillage to 15 cm) and three types of winter cover cropping [bare fallow as control, hairy vetch (Vicia villosa Roth), and rye (Secale cereale L.)] were conducted from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Christensen et al (2012) compared fungal biomass and fungivorous nematodes between conventional and organic fields in Denmark and reported that higher inputs of crop residue enhanced fungal biomass and fungivorous nematodes abundance. Nakamoto et al (2012) also reported that both rye and hairy vetch cover crops increased microbial activities and improved soil aggregate stability with increasing SOC. Zhaorigetu et al (2008) also reported that the use of a rye cover crop increased fungal biomass near the soil surface.…”
Section: Berkelmansmentioning
confidence: 95%
See 2 more Smart Citations
“…Christensen et al (2012) compared fungal biomass and fungivorous nematodes between conventional and organic fields in Denmark and reported that higher inputs of crop residue enhanced fungal biomass and fungivorous nematodes abundance. Nakamoto et al (2012) also reported that both rye and hairy vetch cover crops increased microbial activities and improved soil aggregate stability with increasing SOC. Zhaorigetu et al (2008) also reported that the use of a rye cover crop increased fungal biomass near the soil surface.…”
Section: Berkelmansmentioning
confidence: 95%
“…Crop residue quality and incorporation of residues in the soil also affects the decomposition process. Nakamoto et al (2012) determined the fungal-to-bacterial biomass ratio by a substrate-induced respiration-inhibition approach, suggesting that for a cover crop with a higher C:N ratio, such as rye, incorporation increased fungal biomass more than for a cover crop with a lower C:N, such as hairy vetch, and that crop residue cover on soil surfaces by NT also enhances fungal biomass more than does the incorporation of residue by tillage inversion. The relative abundance of fungivorous and bacterivorous nematodes theoretically provides information about fungal and bacterial contributions to decomposition of soil organic matter (Ferris et al, 2001;Vestergård, 2004).…”
Section: Berkelmansmentioning
confidence: 99%
See 1 more Smart Citation
“…Crop residue returned to the soil is an important management practice in mitigating GHG emissions, as its decomposition can generate fluxes of GHGs. Much research has been focused on the implications of crop residue on soil biological activities (Blanco‐Canqui and Lal, 2009; Butterbach‐Bahl et al, 2013; Lehman et al, 2014; Lehman et al, 2015), indicating that an increase in crop residue accumulation on the soil surface increases microbial activity (Karlen et al, 1994; Nakamoto et al, 2012; Wienhold et al, 2013). Jin et al (2014) hypothesized that removing plant residue from the soil surface may decrease GHG fluxes by reducing the microbial substrate.…”
mentioning
confidence: 99%
“…While grains and vegetables require bacterial dominance or a balance between fungi and bacteria, orchard trees need a dominance of fungi, which are more effective at immobilizing nutrients, Organic Fertilizers preventing leaching. For grasslands, higher F/B ratios are an indication of more sustainable systems, with less environmental impacts [92]. It should be noted that biomass in itself is not a complete indicator for fungal and microbial activity [92] and that the distribution across various depths is also important for fertility and GHG flux dynamics.…”
Section: The Role Of Soil Health and Microbial Activitymentioning
confidence: 99%